Resiliensi Siswa Selama Proses Pembelajaran Jarak Jauh: Korelasi Self-Regulation di Masa Pandemi Covid-19 di SMA Bangka (Jurnal Sustainable, 2022)
This study aims to explain the effect of self-refulation abilities on student resilience during the distance learning process during the Covid-19 pandemic at Bangka High School. The overall result of the calculation of self-regulation with a cumulative score percentage of 82.36% with a very high category. While the student resilience variable during the distance learning process during the covid 19 pandemic at Bangka High School with a cumulative value percentage of 76.01% in the high category. The significance level obtained through the two variables tested through correlation and regression tests has a significance of 0.00. Meanwhile, the results of the determination test show that self-regulation has an effect on student resilience during the distance learning process by 61.1%. While the rest (100% -61.1 = 38.9%) is influenced by other variables or variables that are not examined